School transitions as a turning point for gang status - Carson, Dena C. (Journal of crime and justice, 2017)
The study of gangs corresponds well with life course perspectives of crime as the onset, persistence, and desistance from crime parallel the stages of gang membership. This literature commonly draws on turning points to explain the onset and desistance from criminal behavior, which are often synonymous with life transitions such as marriage, military duty, employment -even gang membership itself. In this study we draw on life course perspectives to examine the impact of a specific life transition that is common during adolescence, school transitions, on a youth’s gang status as well as variables associated with a turning point in the life course. Specifically, we focus on two competing relationships that school mobility can serve as the impetus for joining a gang, or alternatively, act as a ‘hook for change’ and facilitate gang leaving. We use a mixed-methods approach by first drawing on qualitative data that examined desisted gang members and their interpretation of their school transition experiences. Second, consistent with a grounded theory approach, we examined these relationships quantitatively using a panel study of youth followed over a five-year period.